Identification of Potential Inhibitors From Urginea indica Metabolites Against Xanthomonas oryzae pv. oryzae and Magnaporthe oryzae Receptors - Mansoori, Aadil; Dwivedi, Anurag; Sharma, Kapil; Dubey, Sharad Kumar; Thakur, Tarun K.; Kumar, Anirudh (Frontiers in Agronomy, 2022)
Synthetic pesticides are extensively used in agriculture to control pests and prevent yield loss. However, excessive use imposes a serious threat to human health, environment, and biodiversity; hence, certain pesticides have been abandoned from agricultural applications. Thus, there is a need to discover potential and eco-friendly pesticides for the effective management of phytopathogens. In current study, Urginea indica bulb extract was evaluated for potential antimicrobials and antioxidant phytochemicals. The methanol and aqueous extracts were prepared from the bulbs of Urginea indica and were evaluated for polyphenol contents, alkaloid, total antioxidant capacity, and iron chelating activity. Aqueous extract exhibited high phenol and flavonoid content, whereas the total antioxidant activity was higher in methanol extract. The iron chelating activity of both methanolic and aqueous extracts was approximately similar. The antioxidant activity of both methanolic and aqueous extracts was expressed in terms of IC50 values for 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis-3-ethylbenzotiazolin-6-sulfonic acid (ABTS), and nitric oxide (NO). The highest IC50 value was observed for DPPH and the lowest for NO in both the extract. Further, fourier transform infrared spectroscopy (FTIR) was performed, which indicated the presence of several functional groups in the extract. In addition, 75 metabolites were recorded through gas chromatography–mass spectrometry (GC-MS), of which 23 were predicted to have antimicrobial activities. Consequently, metabolites were docked with D-alanine-D-alanine ligase A (DdlA) and mitogen-activated protein kinase 1 (MAPK1) of Xanthomonas oryzae pv. oryzae (Xoo) and Magnaporthe oryzae (M.oryzae), respectively, to understand the possible mechanism of interaction between active metabolites and pathogen receptors. Docking study revealed that quinic acid, 3-caffeoyl has highest binding affinity for both DdlA and MAPK1 with respect to reference compound D-cycloserine and Trametinib. Thus, quinic acid, 3-caffeoyl could inhibit both DdlA and MAPK1-mediated signal transduction and, hence, could be used as a promising natural inhibitor of DdlA and MAPK1 receptors. The above results indicate that Urginea indica could be a potential source of bioactive compounds and could be used as a potential source of natural pesticides to suppress phytopathogens.